Perlindungan Hukum terhadap Pelanggaran Hak Cipta Buku; Tinjauan Hak Ekonomi dan Hak Moral Menurut Undang-Undang No. 28 Tahun 2014 - Fadhli, Rifqi Naufal; Silalahi, Wilma (IAIN Langsa, 2025)
This study aims to analyze the forms of legal protection against book copyright infringement, particularly in terms of economic rights and moral rights as regulated in Law No. 28 of 2014 on Copyright. The main contribution of this research is to provide a deeper understanding of the legal protection mechanisms available to book authors, as well as the role of the government and society in upholding respect for intellectual works. This article falls under the category of normative juridical research with a qualitative approach, analyzed through a literature review of statutory regulations, legal literature, and related documents. The findings of the study conclude that although the law provides a strong legal framework, the implementation of protection for the economic and moral rights of book authors remains suboptimal due to weak law enforcement and low public awareness of the importance of copyright.